Coronary Computed Tomography Angiography as part of initial strategy, in assessment of patients with chest pain – clinical experience and 1 year prognosis. - Han Bing, Chow; H. S., Ling; E. Z., Chan; B. K., Chung; L. K., Then; I. X., Pang; S. T., Chan; H. K., Khor; C. T., Tan; Y. Y., Oon; K. T., Koh; Y. L., Cham; et al. (Elsevier B.V., 2022)
Background: Coronary computed tomography angiography (CCTA) has been showed to have high specificity and sensitivity for detecting coronary artery disease (CAD). In Malaysia, national guidelines state that CCTA may be used in low- to intermediate pre-test probability (LI-PTP) of CAD, who have an equivocal functional test result, and who are asymptomatic or mildly symptomatic with good exercise capacity. Recent evidence suggested a ‘CCTA-first’ strategy in the evaluation of a patient with chest pain could provide prognostic benefits. Prognostic benefits of adopting this strategy in Malaysia has not been well studied.